Strategi Pengadaan Sumber Daya Insani Dalam Meningkatkan Efektivitas Kinerja Perusahaan Pada CV Harapan Tani Nusantara - Siti Nur Aisyah; Hendi Yoga Pratama; Ifroh Naila Riska; Alfi Nur Hasanah; Nurul Setianingrum (CV. ITTC INDONESIA, 2025)
This study aims to examine the human resource procurement strategies implemented by CV Harapan Tani Nusantara and how these strategies contribute to enhancing the effectiveness of the company's performance. Using a descriptive qualitative approach, data was collected through interviews, observations, and document studies. The results indicate that CV Harapan Tani Nusantara implements recruitment strategies through social media, selection based on qualifications, as well as systematic placement and training of employees. Challenges faced include low employee retention due to mismatches or lack of commitment. To address this, the company enhances the quality of selection and creates a supportive work environment. A structured human resource procurement strategy has proven to contribute positively to reducing work errors, increasing customer satisfaction, and generating higher production and company revenue.